The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.1289/ehp.5963
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between water concentrations and individual uptake of chloroform: a simulation study.

Abstract: We simulated the relationship between water chloroform concentrations and chloroform uptake in pregnant women to assess the potential extent of exposure measurement error in epidemiologic studies of the health effects of exposure to water disinfection by-products. Data from the literature were used to assign statistical distributions to swimming pool chloroform concentrations, frequency and duration of swimming, showering and bathing, and average tap water consumption. Measured increases in blood chloroform co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
33
0
2

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(39 citation statements)
references
References 31 publications
4
33
0
2
Order By: Relevance
“…Our simulations were based on a correlation of 0.62 between town mean and true maternal TTHM exposure. Although this relationship is typically unknown in observational epidemiologic studies, it is comparable to that observed in previous DBP studies (Whitaker et al, 2003b;King et al, 2004). Whitaker et al (2003b) and King et al (2004) used individual level water usage data to estimate DBP exposure during pregnancy and reported exposure misclassification rates in excess of 40% for town average trihalomethane classification.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Our simulations were based on a correlation of 0.62 between town mean and true maternal TTHM exposure. Although this relationship is typically unknown in observational epidemiologic studies, it is comparable to that observed in previous DBP studies (Whitaker et al, 2003b;King et al, 2004). Whitaker et al (2003b) and King et al (2004) used individual level water usage data to estimate DBP exposure during pregnancy and reported exposure misclassification rates in excess of 40% for town average trihalomethane classification.…”
Section: Discussionsupporting
confidence: 65%
“…Although this relationship is typically unknown in observational epidemiologic studies, it is comparable to that observed in previous DBP studies (Whitaker et al, 2003b;King et al, 2004). Whitaker et al (2003b) and King et al (2004) used individual level water usage data to estimate DBP exposure during pregnancy and reported exposure misclassification rates in excess of 40% for town average trihalomethane classification. The impact of this exposure misclassification on previously reported association is unknown, but additional research is needed to better understand the relative contribution of various sources of measurement error in epidemiologic studies.…”
Section: Discussionsupporting
confidence: 65%
“…However, no data were available to account for these sources of measurement error in our study. In a simulation study, we showed that there is a moderate positive correlation between chloroform in drinking water and uptake of chloroform (Whitaker et al, 2003b).…”
Section: Discussionmentioning
confidence: 92%
“…A modelling study indicated that swimming had a large impact on an individual's level of chloroform uptake, compared to bathing, showering, or drinking water. 11 The ingestion route likely dominates for non-volatile DBP (for example, haloacetic acids, MX). However, since the putative agent(s) for the increased cancer risk is unknown, the evaluation of different exposure pathways can provide clues for the identification of the relevant chemicals and possible mechanisms of action.…”
Section: Discussionmentioning
confidence: 99%